Revisiting Third Cinema: The 80s - Sengupta, Mihika (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Known as Parallel/ Art/ New wave Cinema, realist Indian cinema emerged parallel to the mainstream films as early as the 1930s. With the advent of sound, came singing and dancing dramas as religious epics, which grew popular with the masses, but a number of films catering to social problems and being naturalistic in their depiction also found fans despite being limited only to the classes of people who understood cinema. The decade of art films believed in the auteur theory and opened a new avenue for Indian cinema, using new techniques and cinematic language. While male directors have always ruled the film industry be it commercial or parallel films, women directors had to work it hard to be able to create a space to express themselves. It was the decade of the eighties that saw directors like Sai Paranjpye, Aparna Sen, Kalpana Lajmi, and Mira Nair spread their wings and start off with art-house cinema. It took a long time since then, for women directors to be able to work and make a permanent and notable space for themselves in both parallel and commercial cinema. Thus, the likes of Paranjpye and Sen can be termed as the women pioneers of parallel cinema and be called synonyms of courage. This paper aims to do a content analysis of four films which have been selected as each director’s first film from the 80’s decade. A study of these films will be done, grounded on few parameters like story, depiction of female characters, their dialogues, etc. Written as a link between women directors and films, this study will explore the auteur-ship/author-ship of women directors in portraying or showing women characters on screen and the treatment of narratives/ storytelling way of women directors. How to cite this article: Sengupta M. Revisiting Third Cinema: The 80s. J Adv Res Jrnl Mass Comm 2019; 6(2): 23-31.